Full-length transcriptome analysis provides insights into larval shell formation in Mulinia lateralis - Guo, Xiaolin; Li, Xixi; Zhao, Feng; Liu, Danwen; Yang, Zujing; Li, Moli; Li, Yajuan; Wei, Huilan; Wang, Hao; Qin, Zhenkui; Zhang, Zhifeng; Bao, Zhenmin (Frontiers in Marine Science, 2023)
Mollusca is the second largest animal phylum and represents one of the most evolutionarily successful animal groups. Mulinia lateralis, a small bivalve is a promising model organism to facilitate studies of molluscs development. However, because of the lack of published genomic and transcriptomic resources, an integrated research on the formation of larval shell in this species, which is a representative developmental process of molluscs and of great importance for larva survival, is hindered. In this study, the blastula, gastrula, trochophore larva and D-shaped larva of M. lateralis were utilized for generating a comprehensive full-length transcriptome through PacBio Isoform-sequencing (Iso-seq) and Illumina RNA-Seq. A total of 238,919 full-length transcripts with an average length of 3,267 bp and 121,424 annotated genes were obtained. Illumina RNA-Seq data analysis showed that 4512, 10637 and 17829 differential expression genes (DEGs) were obtained between the two adjacent developmental stages. Functional annotation and enrichment analysis revealed the specific function of genes in shell biomineralization during different developmental stages. Twelve genes that may be involved in the formation of larval shell of M. lateralis were identified, including insoluble shell matrix protein encoding gene 1 (ISMP1), ISMP2, ISMP5, chitin synthase, tyrosinase, chitin-binding protein, collagen and pu14 involved in shell matrix deposition, and carbonic anhydrase, solute carrier family 4 member 8 (slc4a8), EF-hand and a calmodulin coding gene C-2442 participated in ion transportation. In addition, calcium ion binding function, calcium signaling pathway and endocrine and other factor-regulated calcium reabsorption pathways were significantly enriched. WGCNA analysis identified two modules that related to biomineralization and larval shell formation, and slc4a8 as well as ring finger protein 41 (rnf41) were key hub genes may involve in this process. Besides, it could be implied that the process of ion transport occurs earlier than the deposition of shell matrix. This work provided a clear view of the transcriptome for M. lateralis and will be valuable in elucidating the mechanisms of larval shell formation as well as other developmental process in molluscs.